2002
DOI: 10.1177/01461672022811009
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Gender-Related Constructs in Dating Aggression

Abstract: This study examined frequency and severity of physical, symbolic, and psychological aggression between college men and women in 85 heterosexual dating relationships and the extent to which gender role constructs predicted reports of aggression. Although there were no differences on self-reports of perpetration, men reported higher victimization levels than women and higher physical and psychological victimization levels than perpetration levels, whereas women reported higher symbolic perpetration levels than v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 58 publications
8
55
1
3
Order By: Relevance
“…Estos hallazgos se contraponen a los diversos estudios que indican una mayor tendencia de las mujeres a cometer actos agresivos de tipo psicológico/verbal (e.g. Corral y Calvete, 2006;Hird, 2000;Malik et al, 1997;Muñoz-Rivas, Graña et al, 2007b;Muñoz-Rivas, González, Graña y Peña, 2007;Riggs y O'Leary, 1996) y de tipo fí-sico medio como bofetadas, agarrones o empujones (e.g., Clark, Beckett, Wells y Dungee-Anderson, 1994;Follingstad, Wright, Lloyd y Sebastian, 1991;Foshee, 1996;Gray y Foshee, 1997;Jenkins y Aube, 2002;Sears, Byers y Price, 2007;Sharpe y Taylor, 1999). A pesar de que la literatura indica mayoritariamente que, en las relaciones de noviazgo, las mujeres cometen más actos agresivos que los hombres, entendemos que podría deberse a que no son tan reacias como los hombres a expresar que abofetean o empujan a sus parejas, probablemente por la mayor tolerancia social (potenciada por el cine y la publicidad) de las agresiones medias cuando son perpetradas por las mujeres (González y Santana, 2001).…”
Section: Discussionunclassified
“…Estos hallazgos se contraponen a los diversos estudios que indican una mayor tendencia de las mujeres a cometer actos agresivos de tipo psicológico/verbal (e.g. Corral y Calvete, 2006;Hird, 2000;Malik et al, 1997;Muñoz-Rivas, Graña et al, 2007b;Muñoz-Rivas, González, Graña y Peña, 2007;Riggs y O'Leary, 1996) y de tipo fí-sico medio como bofetadas, agarrones o empujones (e.g., Clark, Beckett, Wells y Dungee-Anderson, 1994;Follingstad, Wright, Lloyd y Sebastian, 1991;Foshee, 1996;Gray y Foshee, 1997;Jenkins y Aube, 2002;Sears, Byers y Price, 2007;Sharpe y Taylor, 1999). A pesar de que la literatura indica mayoritariamente que, en las relaciones de noviazgo, las mujeres cometen más actos agresivos que los hombres, entendemos que podría deberse a que no son tan reacias como los hombres a expresar que abofetean o empujan a sus parejas, probablemente por la mayor tolerancia social (potenciada por el cine y la publicidad) de las agresiones medias cuando son perpetradas por las mujeres (González y Santana, 2001).…”
Section: Discussionunclassified
“…These and other gender differences are evident in studies of different perceptions and meanings attributed by men and women to aggression [Archer and Haigh, 1997a;Bettancourt and Miller, 1996;Byrne and Arias, 1997] and fear of crime, such as fear from being a victim of violence [Goodey, 1994;Haghihi and Sorenson, 1996;Thompson et al, 1992]. It has also been demonstrated that women are more likely to self-report aggressive behavior than men in intimate relationships [Jenkins and Aube, 2002;Straus et al, 1980]. However, it is important to note that there are differing opinions on this finding [see: Johnson and Ferraro, 2000;White et al, 2000].…”
Section: Gender Differences In Aggressionmentioning
confidence: 99%
“…Jenkins and Aube Jenkins (2002) stated that women, in comparison to men, are in fact more aggressive in some conditions, and thus more likely to kick, hit or physically assault their husbands. Meanwhile, there is a controversy in the intimate partner violence (IPV) related to the rates and consequences of women's use of aggression against the men they love.…”
Section: Higher Physical Aggression In Women Compared To In Menmentioning
confidence: 99%